Protection of young consumers from the influence of advertising of foods high in fat, sugar, salt and sweetened carbonated beverages - is it possible? - Kosiorowska, Małgorzata, 1978-
Vplyv reklamy nezdravých potravín na mladého spotrebiteľa. Odporúčania WHO a tiež sebaregulácie v tejto oblasti.